1994
DOI: 10.1088/0963-0252/3/4/007
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of heavy particles in the expanding plasma jet in argon

Abstract: Th's paper concerns the behaviox of neavy particles in an argon plasma expanding from a cascaded arc. The pasma 's characterize0 Jsing high-acc-racy spatially resolved Thomson-Rayleigh measJrements. Iris shown that the expans'on of tne neavy particles, neutral part'cles and :ons, is cose to adiaDatic and that three-particle recombnaion has a small effect on the ion density. The measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 27 publications
7
58
1
Order By: Relevance
“…15 it can be observed that in the first centimeters of the expansion, on axis the electron density at 88.3 Pa is higher than at 9.7 Pa. This is in agreement with the trends reported by van de Sanden et al [2,3,29], who measured electron densities in argon expanding plasmas at different background pressures.…”
Section: Stationary Shock and Background Pressuresupporting
confidence: 91%
See 4 more Smart Citations
“…15 it can be observed that in the first centimeters of the expansion, on axis the electron density at 88.3 Pa is higher than at 9.7 Pa. This is in agreement with the trends reported by van de Sanden et al [2,3,29], who measured electron densities in argon expanding plasmas at different background pressures.…”
Section: Stationary Shock and Background Pressuresupporting
confidence: 91%
“…Subsequently, dissociative recombination of an electron with the molecular ion, producing two hydrogen atoms, results in an efficient loss channel for electrons. Under our gas flow and gas pump conditions the residence time is larger than the transit time of the plasma from the nozzle exit to the other end of the reactor [29]. This means that particles, mainly H 2 , will recirculate several times before being pumped out of the reactor.…”
Section: Effect Of the Background Pressurementioning
confidence: 97%
See 3 more Smart Citations